Integrated GC-MS and UPLC-ESI-QTOF-MS based untargeted metabolomics analysis of in vitro raised tissues of Digitalis purpurea L - Bansal, Yashika; Mujib, A.; Mamgain, Jyoti; Syeed, Rukaya; Mohsin, Mohammad; Nafees, Afeefa; Dewir, Yaser Hassan; Mendler-Drienyovszki, Nóra (Frontiers in Plant Science, 2024)
Digitalis purpurea L. is one of the important plant species of Nilgiris, Kashmir and Darjeeling regions of India, belonging to the family Plantaginaceae, with well-known pharmacological applications. In the present investigation, an in vitro culture technique of indirect shoot organogenesis of D. purpurea is being explored; the biochemical attributes, the antioxidant activities and the metabolomic analyses were made by utilizing untargeted Gas Chromatography-Mass Spectrometry (GC-MS) and Ultra Performance Liquid Chromatography coupled with electronspray ionization/quadrupole-time-offlight-mass spectrometry (UPLC-ESI-QTOF-MS) approaches. Initially, the leaf explants were used for callus induction and proliferation and maximum callusing frequency (94.44%) and fresh biomass (4.9 g) were obtained on MS, fortified with 8.8 µM BAP (6-benzyl amino purine) + 0.9 µM 2,4-D (2,4dichlorophenoxyacetic acid), subsequently shoot formation (indirect organogenesis) was noted on the same MS medium with a shoot induction frequency of 83.33%. Later on, the biochemical and antioxidant potential of in vivo-, in vitro grown leaf and leaf derived callus were assessed. Significantly higher total phenol, flavonoid, DPPH (2,2-diphenyl-1-picrylhydrazyl), POD (peroxidase) and SOD (superoxide dismutase) activities were noticed in in vitro grown callus and leaf tissues compared with field grown leaf. The GC-MS analysis of each methanolic extract (in vivo-, in vitro derived leaf and leaf derived callus) displayed the presence of more than 75 bioactive compounds viz loliolide, stigmasterin, alpha-tocopherol, squalene, palmitic acid, linoleic acid, beta-amyrin, campesterol etc. possessing immense therapeutic importance. The UPLC-MS based metabolite fingerprinting of each methanolic extracts were conducted in both positive and negative ionization mode. The obtained results revealed variation in phytochemical composition in field -and laboratory grown tissues, indicating the impact of in vitro culture conditions on plant tissues. The detected phytocompounds belongs to various classes such as flavonoids, steroids, terpenoids, carbohydrates, tannins, lignans etc. The medicinally important metabolites identified were 20, 22-dihydrodigoxigenin, digoxigenin monodigitoxoside, apigenin, luteolin, kaempferide, rosmarinic acid, nepitrin and others. The results of the present study suggest that in vitro culture of D. purpurea could successfully be utilized for the novel drug discovery